2001
DOI: 10.1007/s004210100423
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in postural control in humans in response to a sudden deceleration generated by postural disturbance

Abstract: Age-related differences in postural control in response to a relatively large deceleration resulting from postural disturbance were investigated in eight normal elderly men (age range 67-72 years) and eight young men as controls (age range 19-22 years) using a moving platform. Data were obtained for the hip, knee and ankle angles, position of the centre of foot pressure (CFP), head acceleration, and muscle activity of the leg muscles. The elderly subjects had slower and larger ankle and hip joint movements, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 27 publications
(40 reference statements)
3
25
0
4
Order By: Relevance
“…The CCI results in this study were in agreement with previous studies (Hsu et al, 2007;Okada et al, 2001) that older fallers and non-fallers had greater knee CCI than younger adults. The greater stance knee CCI (and also stiffness) among older non-fallers could indicate that they have more difficulty with coordination and controlling postural stability during stepping forward movement than younger adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The CCI results in this study were in agreement with previous studies (Hsu et al, 2007;Okada et al, 2001) that older fallers and non-fallers had greater knee CCI than younger adults. The greater stance knee CCI (and also stiffness) among older non-fallers could indicate that they have more difficulty with coordination and controlling postural stability during stepping forward movement than younger adults.…”
Section: Discussionsupporting
confidence: 93%
“…In other words, increased co-contraction can result in declining ability to maintain balance during static/ dynamic (e.g., standing/stepping) tasks (Horak et al, 1992). During forward stepping, cocontraction of vastus lateralis and medial hamstrings has been used to stabilize motion (Tseng et al, 2007) and older adults have been shown to have greater co-contraction than younger adults (Hsu et al, 2007;Okada et al, 2001). These age-related increases in cocontraction could also play a role in MSL kinetics, but these data have not yet been recorded during the MSL.…”
Section: The Maximummentioning
confidence: 99%
“…The elderly rely more on hip movements, while young people rely on ankle movements to control postural stability. 26 A decline in somatosensory information from the feet is a major factor in this pattern change with age. 27 Therefore the considerable impact of tai chi practice on ankle proprioception is of great benefit in the retention of balance control in old people.…”
Section: Discussionmentioning
confidence: 99%
“…This could be expected from the slower and larger movements of older subjects in response to support-surface perturbations (Okada et al 2001). Associations of T H with isokinetic strength and the rate of force development suggest that they are determinants of T H .…”
Section: Age-related Changesmentioning
confidence: 92%